Enigma of Relationship between Digital Economy and Intellectual Property Rights: Reflections on Innovation in Digital Economy Represented by Cloud Computing - Zhang, Weier; Zhang, Yiyi (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The development of the digital economy and intellectual property management represented by cloud computing has promoted the progress of China's modernization road. Cloud computing plays a vital role in various industries, and the control of intellectual property rights in the digital economy represented by cloud computing is closely connected with the high-quality development of China's digital economy, the construction of a robust intellectual property country, and the modernization of the national government. China's intellectual property management capability and digital economy management system are advanced, but practical difficulties still exist at home and abroad.OBJECTIVES: To improve the development level of computer information technology such as cloud computing; to promote the integrated development of digital economy and intellectual property rights; to solve the protection problems in the practical application of intellectual property rights with information technology; and to promote the coordinated development of digital economy and intellectual property rights represented by cloud computing.METHODS: Analyzes the role of intranet in protecting business information from the technical perspective of cloud computing; puts forward the hypothesis of the relationship between the digital economy and intellectual property rights by using literature research; and applies the empirical method to verify the use of patent data of state-owned enterprises and the total index of the regional digital economy.RESULTS: The results of the study show that there is a significant positive correlation between the level of development of cloud computing, the Digital Economy, and the internal cloud computing network of the company, which meets the external conditions of the lack of capacity of the Digital Economy and strengthens the globalization of the cloud computing cooperation network.CONCLUSION: Companies can manage the risk of data loss in the digital economy by adapting their internal cloud computing capabilities. After in-house processing and multiple reliability tests, the impact of the digital economy, represented by cloud computing, on supply chain innovation remains significant. In the post-financial crisis era, the effect of the digital economy on chain innovation is important because it is a cloud computing technology-intensive production chain with low dependence on external technologies. The digital economy has a threshold effect on innovation in the production chain. With the strengthening of intellectual property protection, the marginal impact of cloud computing and the digital economy on chain innovation increases significantly.
Keywords: digital economy; intellectual property; innovation; cloud computing